Humor in Structure: An Analysis of Coordinating Conjuctions in Compound sentences from Adam Sandler’s Best of The Sandman - Febrian yosua Sakalessy; Ni Putu Cahyani Putri Utami (Universitas Islam Negeri Palopo, 2025)
This study examines the syntactic function of coordinating conjunctions in compound sentences within the transcript of Adam Sandler’s stand-up comedy video Best of The Sandman. It focuses on syndetic coordination and the constituent structure of compound sentences, illustrated through tree diagrams. The data were collected through observation by transcribing and analyzing the comedic monologue. This qualitative study draws on three linguistic frameworks: Oshima & Hogue (2007) for sentence type classification, Aarts et al. (2006) for coordination theory, and Brown & Miller (2020) for syntactic structure analysis. The findings reveal that only four of the seven FANBOYS coordinating conjunctions were used in the transcript and, but, or, and so with and being the most frequent, appearing in 67 out of 81 compound sentences (82.72%). Coordinating conjunctions are shown to play a crucial role in shaping humor and maintaining coherence throughout the performance. The tree diagram analysis further clarifies the syntactic relationships within compound sentences, underscoring the value of syntax in understanding spoken discourse in comedic contexts.